Agency matters! Social preferences in the three-person ultimatum game - Alexopoulos, Johanna; Pfabigan, Daniela M.; Göschl, Florian; Bauer, Herbert; Fischmeister, Florian P. (Frontiers in Human Neuroscience, 2013)
In the present study EEG was recorded simultaneously while two participants were playing the three-person Ultimatum Game. Both participants received different offers from changing proposers about how to split up a certain amount of money between the three players. One of the participants had no say, whereas the other, the responder, was able to harm the payoff of all other players. The aim of the study was to investigate how the outcomes of the respective other are evaluated by participants who were treated fairly or unfairly themselves and to what extent agency influences concerns for fairness. Analyses were focused on the medial frontal negativity (MFN) as an early index for subjective value assignment. Recipients with veto-power exhibited enhanced, more negative-going, MFN amplitudes following proposals that comprised a low share for both recipients, suggesting that responders favored offers with a fair amount to at least one of the two players. Though, the powerless players cared about the amount assigned to the responder, MFN amplitudes were larger following fair compared to unfair offers assigned to the responder. Similarly, concerns for fairness which determined the amplitude of the MFN, suggested that the powerless players exhibited negative and conversely the responders, positive social preferences.